What is discourse analysis? - Taylor, Stephanie, 1954- (2013)
This is an accessible introductory guide to a popular and widely-used qualitative research approach which is widely used in the social sciences and related disciplines. This book explores the idea of how meaning is socially constructed and how talk and text can be interpreted. The challenges of discourse analysis are outlined as well as helpful ways to approach them - from finding the right starting point, processing and interpreting data through to building an argument. Discourse analysts work with language data, including talk, documents and broadcast material. Researchers in different traditions study interactions and social practices, meaning-making and larger meaning systems, and contests and conflicts around collective identities, social norms and subjectification. What is discourse analysis? addresses new researchers and other academics interested in language and its associated practices. The book outlines the history of discourse analysis, its key concepts and theorists, and its uses and challenges. Discussions of published studies illustrate the use of the approach to investigate a range of research topics, such as gender, health and national identities.
Machine generated contents note: 1.Introduction -- 2.Theories and common concerns -- 3.Four examples of discourse analysis -- 4.The usefulness of discourse analysis for social science researchers -- 5.The challenges of discourse analysis -- 6.Criticisms of discourse analysis -- 7.Summary.
Includes bibliographical references (pages 103-109) and index.
Keywords: Discourse analysis; Discourse analysis